Co-generation, sharing and transfer of technologies in Small and Medium agrifood Enterprises (SMEs) - Petruzzella D.; Semeraro M.; Ciaula M.; Fiume P. (Innovation in the Mediterranean agrifood sector. Concepts, experiences and actors in a developing ecosystem, 2016)
The chapter focuses on the results of the INTRA Project (Introducing innovations in traditional agrifood products to increase SME competitiveness). This initiative belongs to the Greece-Italy territorial cooperation programme and aims to strengthen the services for sharing and transfer of innovations in the agrifood sector. INTRA has focused on analysing the innovation needs of traditional Italian and Greek businesses, beginning with experiences collected in Apulia (Italy) and the Ionian Islands (Greece), in order to propose possible methodologies and tools for improving the efficiency of the innovation supply chain. Coordinated by CIHEAM-Bari, the project has involved the participation of the Ionian University, the regions, and the Brindisi and Corfu chambers of commerce. This work has created a database, intended as a system for collecting the innovation needs of businesses and as a concrete system for increasing their active involvement in the new collaborative bottom-up agrifood innovation paradigm. The conclusions propose strategies for reducing the cultural and geographical divide separating the innovators developing new projects from businesses and public authorities. Annex 1 contains a detailed examination of the INTRA Database.